The Role of Magnetic Resonance Imaging in Preoperative Evaluation of Perianal Fistula Taking Operative Findings as Gold Standard - Shahzad , Hooria; Ahmad , Mian Waheed; Ghaffar , Sidra; Aslam , Arslan; Anayatullah, Maryam; Shafique , Adeela (Indus Journal of Bioscience Research, 2025)
Background: Perianal fistulas are common anorectal disorders that pose significant challenges in surgical management. Accurate preoperative evaluation is crucial for effective treatment planning. Objective: To evaluate the diagnostic accuracy of MRI in identifying perianal fistulas, including the primary fistulous tract, secondary extensions, and associated abscesses, and to compare MRI findings with intraoperative findings. Methods: This cross-sectional study was conducted at the Department of Diagnostic Radiology, Gujranwala Teaching Hospital, Gujranwala. A total of 98 patients (50 male, 48 female) aged 18-60 years with suspected perianal fistulas were enrolled through non-probability consecutive sampling. MRI was performed using a 1.5 Tesla superconducting magnet. The presence, type, and anatomical location of fistulas were assessed and compared with operative findings. Results: The sensitivity of MRI was 93.18%, with a specificity of 100%. The positive predictive value (PPV) was 96.47%, and the negative predictive value (NPV) was 84.61%. MRI accurately identified the primary fistulous tract in 62 patients, secondary extensions in 23 patients, and abscesses in 30 patients. The overall diagnostic accuracy of MRI was 94.9%. There were minor discrepancies between MRI and operative findings, with a small number of false negatives (2%) and false positives (3%). Conclusion: It is concluded that MRI is a highly sensitive and specific imaging modality for the preoperative evaluation of perianal fistulas. It provides accurate diagnostic information that aids in surgical planning, especially in identifying complex fistulas and abscesses. The high positive predictive value indicates that MRI is reliable for confirming the presence of fistulas, while the negative predictive value suggests that MRI findings should be carefully interpreted in cases of negative results.